PENERAPAN PEMBELAJARAN AL-QUR’AN MELALUI METODE WAFA DENGAN MENGGUNAKAN MEDIA KARTU GAMBAR DAN ALAT PERAGA TERHADAP KEMAMPUAN BACAAN DI TK TERPADU PUTERA ZAMAN - Nisanabila, Khairun; Ulum, Mohammad Samsul (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
The wafa method is a comprehensive and comprehensive approach to learning the Qur'an that utilizes the right and left hemispheres of the brain. The Wafa method is referred to as the right brain approach, which utilizes the senses of touch, sight, and hearing, to facilitate learning.The purpose of this study is to describe the implementation of Al-Qur'an learning, the achievement of the development of Al-Qur'an learning outcomes, and the superiority of Al-Qur'an learning through the Wafa method using picture card media and props on reading skills at Putera Zaman Integrated Kindergarten.The results showed that, (1) The implementation of Al-Qur'an learning through the Wafa method is very conducive and vibrant, because the ustadzah is good at teaching by using gestures to provoke enthusiasm and minimize student boredom. (2) The achievement of the development of Al-Qur'an learning outcomes through the Wafa method, including starting to develop, is characterized by indicators, students concentrate when learning the Al-Qur'an, students are serious when learning the Al-Qur'an and students follow Al-Qur'an learning activities from beginning to end. (3) The advantages of learning the Qur'an through the wafa method can make students enthusiastic about Qur'anic education.